Case report: Sclerosing encapsulating peritonitis in a cat with disseminated pancreatic adenocarcinoma of presumed ductal origin - Kim, Chaerin; Kim, Sanggu; Park, Jinhyeong; Lee, Dohee; Chae, Yeon; Yun, Taesik; Chang, Dongwoo; Kang, Byeong-Teck; Lee, Sungin; Kim, Soochong; Kim, Hakhyun (Frontiers in Veterinary Science, 2024)
A 9-year-old, neutered male, domestic short-haired cat was referred for recurrent ascites of unknown etiology over a week. Physical examination revealed abdominal distension and ultrasonography revealed a large volume of ascites throughout the abdominal cavity; this was interpreted as modified transudate. The mesentery and abdominal fat were hyperechoic and edematous. Fat tissue was assessed using fine-needle aspiration cytology, and adipocytes, fat-phagocytizing macrophages, and neutrophils were identified. Computed tomography revealed a pancreatic mass connected to the left pancreatic leg. Exploratory laparoscopy confirmed nodular masses and organ adhesions, leading to a tentative diagnosis of sclerosing encapsulating peritonitis. The cat was administered prednisolone, vitamin E, and tamoxifen but died 22 days after the initial therapy. Necropsy revealed a multi-lobulated pancreatic tumor (10 × 10 cm) tightly attached to the stomach and intestine, with a large amount of ascites. The peritoneum, stomach, intestine, and mesentery were covered with numerous disseminated nodules of various sizes (1–5 mm diameter). Microscopically, the tumor consisted of extensive adipose tissue, locally extensive inflammatory infiltrates, fibrous connective tissue, and small invasive proliferative glands. Well-defined small irregular glands composed of single-layered epithelial cells that appear to be of ductal origin were surrounded by an abundant desmoplastic stroma. Neoplastic nodules were widespread in the liver, stomach, peritoneum, mesentery, mesenteric lymph nodes, lungs, and urinary bladder. Immunohistochemistry revealed that the neoplastic glands were positive for pan-cytokeratin, confirming the pancreatic epithelial origin of the tumor. This is the first report of sclerosing encapsulating peritonitis accompanied by aggressive pancreatic adenocarcinoma of presumed ductal origin and extensive metastasis in a cat.